Analysis of genetic polymorphism as risk factor of diabetes nephropathy among type 2 diabetic patients of a tertiary hospital - Yahya, Mohd Jokha (2017)
Type two diabetes mellitus (T2DM) is one of the most common multifactorial disorders associated with significant risk of nephropathy. Nephropathy is common among the diabetic patients and the prevalence is high and increasing. Unfortunately the genetic aspect behind this was minimally studied in Malaysia. Genetic analysis of the polymorphism and susceptibility provides best apprehension on the pathogenesis elevating to innovative therapeutic approaches in patient management. The aim of this study was to determine the association of Carnosinase (CNDP1-D18S880 and rs2346061), Endothelial nitric oxide synthase (NOS3-rs1799983), Engulfment and cell mortality (ELMO1-rs74130), Manganese superoxide dismutase (MnSOD-rs4880) Methylene tetrahydrofolate reductase (MTHFR-rs1801133), Monocyte Chemoattractant protein-1 (CCL2-rs3917887), Chemokine receptor 5 (CCR5- rs1799987), Matrix Metalloproteinase-9 protein (MMP9-rs17576) and Interleukin-8 (IL8-rs4073) polymorphism to T2DM nephropathy among Malaysian. These nine genes were selected based on their function in the development of nephropathy in T2DM. IL8, CCR5, CCL2 ELMO1 are related to pro-inflammatory effect while CNDP1, NOS3, MnSOD are related to oxidative stress. MMP9 is related to the homeostasis of extracellular matrix and changes of MTHFR enzymatic activity is considered as contributing to development of T2DM nephropathy. More than one thousand diabetic patients were examined and a total of 652 T2DM patients were tested comprising 227 Malays (non-nephrotic=96 and nephrotic=131), 203 Chinese (nonnephrotic= 95 and nephrotic=108) and 222 Indians (non-nephrotic=136and nephrotic=86). For the D18S880 of CNDP1, sequencing the gene was the most appropriate approach while the rest are tested by Mass ARRAY to identify the polymorphisms. The alleles and genotypes were tested using 4 genetic models and the best mode of inheritance was chosen. It was found that 7 of the 10 polymorphisms tested were significantly associated with nephropathy in T2DM in this study. The rs2346061 of CNDP1 was significantly associated among the Indians only with OR=1.94 (1.76-3.20) CI=95% fitted best the multiplicative model and D18S880, another polymorphism of CNDP1 was associated among all the three major races with the Malays having the highest risk with OR=2.46 (1.48-4.10) CI=95%, Chinese OR=2.26 (1.34-3.83) CI=95% and Indians OR=1.77 (1.18-2.65) CI=95%. Meanwhile, the remaining 5 polymorphisms suit best with the additive mode of heritance. MnSOD, rs4880 among the Chinese subjects had OR=2.8 (0.53-14.94) 95% CI, Indians OR=2.4 (0.69-2.84) 95% CI and Malays OR=2.16 (0.54-8.65) 95% CI. Looking at NOS3 rs1799983, the Indians OR=3.16 (0.52-17.56) 95% CI followed by Chinese OR=3.55 (0.36-35.03) and the Malays OR=2.89 (0.29-28.32) 95% CI. Meanwhile in proinflammatory gene, CCR5 rs1799987, only the Chinese showed association for this polymorphism, with OR=6.71 (2.55-17.68) 95% CI. The same for IL8 rs4073, only the Indians showed association with nephropathy with OR=1.57 (0.66-3.71) 95% CI. The MMP9 rs17576 variant was found to be significantly associated among the Indians OR=3.91 (1.69-9.03) 95% CI and the Chinese OR=4.38 (1.81-10.59) 95% CI but no association in Malays. In conclusion, this study shows the significant potential of six polymorphisms on the development of T2DM nephropathy. These genes may be considered as risk factors for Malaysian subjects who are predisposed to T2DM nephropathy but differs for different races. Further studies which involve environmental risk factor should be taken into consideration. An individual without any of the polymorphisms may still develop nephropathy due to the, environmental factors such as unhealthy life style.